A CFD-derived correlation for methane heat transfer deterioration. (1st February 2016) - Pizzarelli, Marco
ABSTRACT: Methane heat-transfer deterioration can occur in the regenerative cooling channels of future liquid-oxygen/liquid-methane rocket engines with chamber pressures higher than about 50 bar. Aiming to improve the prediction capabilities for the design of such systems, in the present study, a Nusselt number correlation able to describe the convective heat-transfer characteristics of supercritical flow exhibiting deterioration and with negligible buoyancy effects is obtained using data from numerical simulations. The adopted numerical solver of the Navier–Stokes equations is first validated against the experimental data of near-critical hydrogen in heated tubes and then used to collect heat-transfer data of supercritical methane in a heated tube for different levels of pressure, temperature, and mass flux.